The Group Algebra (I)

[ Note: the contents of this article overlap with a previous series on character theory. ]

Let K be a field and G a finite group. The group algebra K[G] is defined to be a vector space over K with basis \{g : g\in G\}, where “g” here is an abstract symbol for each element g of G. Thus, K[G] has dimension |G| over K. Now K[G] has a ring structure obtained from group multiplication, where the algebra product σ⋅τ is precisely the group product, i.e. an element of G. For example, multiplication in Q[S3] gives

(1∙(1,2) – 3∙ (2,3)) ∙ (2∙ (1,3) + 4e) = 2∙(1,3,2) + 4∙(1,2) – 6∙(1,2,3) – 12∙(2,3).


The most important aspect of the group algebra is that its modules M correspond to group homomorphisms \rho : G \to GL_K(M), of G to the group of invertible K-linear maps M→M; such a ρ is called a representation of G over K. Indeed, if M is a K[G]-module, then considering how elements g ∈ K[G] acts on M (for g ∈ G), we obtain a homomorphism G \to GL_K(M).

Conversely, if we have a group homomorphism \rho : G\to GL_K(M), then this gives M the structure of a K[G]-module by letting \sum_{g\in G} c_g\cdot g (c_g \in K) take m ∈ M to \sum_{g\in G} c_g (\rho(g))(m).

Note that a homomorphism of K[G]-modules fV → W is a linear map of vector spaces such that f(g⋅v) = g⋅f(v) for any g in G and v in V. Such a map is also called an intertwining map (since it commutes with every element of G).

Example 1

Every group has a trivial representation, corresponding to G → K* which maps all g to 1. As a K[G]-module representation, this is V := K and \sum_{g\in G} c_g\cdot g takes every v in V to \sum_{g\in G} c_g v.

Example 2

V := K[G] is a module over the ring K[G]; this corresponds to the regular representation. E.g. if G = {egg2} is the cyclic group of order 3, then the group homomorphism \rho : G \to GL_K(K^3) is given by:

\rho(e) = \begin{pmatrix} 1 &0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1\end{pmatrix}, \quad \rho(g) = \begin{pmatrix} 0 & 0 & 1\\ 1&0&0 \\ 0&1&0\end{pmatrix}, \quad \rho(g^2) =\begin{pmatrix} 0&1&0 \\ 0&0&1 \\ 1&0&0\end{pmatrix}.

Example 3

Let KRG = S3,  MR3 and let \rho : G \to GL(M) be the homomorphism taking g \in S_3 to the linear map

\rho_g : M\to M, \qquad (x_1, x_2, x_3) \mapsto (x_{g^{-1}(1)}, x_{g^{-1}(2)}, x_{g^{-1}(3)}).

E.g. g = (1,3,2) takes (xyz) to (yzx) and h = (1, 2) takes (xyz) to (yxz). The inverse of g is necessary for the subscripts to ensure that \rho_g \rho_h = \rho_{gh} for any g, h\in S_3. Now M is a module over R[S3], where, e.g. a(1, 2) + b(1, 3, 2) takes the point (x, yz) to (ay+byax+bzaz+bx) so its corresponding matrix is \begin{pmatrix} 0 & a+b & 0 \\ a & 0 & b \\ b & 0 & a\end{pmatrix}, assuming elements of M are written as column vectors.


Main Result

Theorem. If the characteristic of K does not divide |G|, then K[G] is semisimple.


We shall prove: for each left ideal I of K[G], there is a left ideal J such that I ⊕ JK[G] (i.e. I ∩ J = 0 and IJK[G]). Assuming this holds, since K[G] is of finite dimension, it must have a minimal left ideal I1. By our assumption, there exists J1 such that I1 ⊕ J1 = K[G]. Again, J1 must have a simple submodule I2 etc . Eventually, we obtain K[G] as a direct sum of minimal left ideals.

Now suppose I is a left ideal of K[G]. This is a vector subspace, so we can write K[G] = I ⊕ W for a subspace W. Let pK[G] → K[G] be the projection I ⊕ WI, so that p2p and p has image I (see # later). Let us now define the K-linear map:

q : K[G] \to K[G], \quad q(\alpha) := \frac 1 {|G|} \sum_{g\in G} g\cdot p(g^{-1} \alpha) for \alpha \in K[G].

[ Note that this is well-defined since |G| is invertible in K. ] We have the following properties of q:

  1. The image of q is in I : indeed image of p lies in I and g⋅I ⊆ I for any g in G.
  2. q(α) = α for all α in I : indeed, g^{-1}\alpha \in I and since p(α) = α for all α in I, the result follows. Together with property 1, this means im(q) = I.
  3. q2: for any α in K[G], we have q(α) in I, so by property 2, q(q(α)) = q(α).
  4. q is a K[G]-module homomorphism: clearly q is K-linear; furthermore for any h in G, we have

h\cdot q(h^{-1}\alpha) = \frac 1 {|G|} \sum_{g\in G} hg\cdot p(g^{-1}h^{-1}\alpha)\stackrel{x=gh}{=} \frac 1{|G|} \sum_{x\in G} x\cdot p(x^{-1}\alpha) = q(\alpha) \implies q(h\alpha) = h\cdot q(\alpha)

Since q2qq is a projection and we have K[G] = ker(q) ⊕ im(q) = ker(q) ⊕ I (see # later). And since q is a K[G]-module homomorphism, its kernel is a submodule, and we have proven our assumption. ♦

[ # Note: along the way, we used the fact that a K-linear map pV → V such that p2p gives us V = ker(p) ⊕ im(p). The proof of this is an easy exercise. ]

From our classification of semisimple rings, we obtain the

Corollary. If char(K) does not divide |G|, then K[G] is isomorphic to a finite product of matrix rings over division rings. Writing K[G] \cong \prod_{i=1}^k M_{n_i}(D_i) and letting m_i = [D_i : K] gives us

|G| = \dim_K K[G] = \sum_{i=1}^k n_i^2 m_i,

where k is the number of isomorphism classes of simple K[G]-modules. [ Note: the simple K[G]-modules are also called irreducible representations of G. ]

This entry was posted in Notes and tagged , , , , , , . Bookmark the permalink.

Leave a Reply

Fill in your details below or click an icon to log in: Logo

You are commenting using your account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )

Connecting to %s